PENGARUH CAPITAL ADEQUACY RATIO, NON PERFORMING LOAN, DAN LOAN DEPOSIT RATIO TERHADAP RETURN ON ASSET PADA PT. BANK MANDIRI (PERSERO) TBK. DAN ENTITAS ANAK PERIODE 2015-2024 - Khoiriyah , Wihdatul; Tohari, Amin; Sri Widiawati , Hestin (Jurnal Manajemen Perbankan Keuangan Nitro, 2025)
This research aims to analyze the effect of Capital Adequacy Ratio, Non Performing Loan, and Loan Deposit Ratio on Retrun On Asset at PT. Bank Mandiri Tbk. and Subsidiaries for the period 2015-2024. This type of research is quantitative research with a comparative causal approach. The subjects studied were PT. Bank Mandiri Tbk. and Subsidiaries. The objects used were quarterly financial report data from PT. Bank Mandiri Tbk. and Subsidiaries for 10 years, namely from 2015-2024 and 40 data were obtained. The data analysis techniques used are descriptive statistics and multiple linear regression analysis. Data processing used SPSS Software version 30. The results showed that partially Capital Adequacy Ratio and Non Performing Loan had a significant effect on Retrun On Asset, while Loan Deposit Ratio did not have a significant effect on Return On Assets. Simultaneously Capital Adequacy Ratio, Non Performing Loan, and Loan Deposit Ratio had a significant effect on Return On Assets.